Cocoa black pod rot incidence across four cocoa-growing ecotopes in Baracoa, Cuba - Casenave-Cambet, Addael Cuscó (2026)
Introduction. Black pod rot caused by Phytophthora spp. reduces global cocoa production. In Baracoa, the main cocoa-producing region of Cuba, climatic conditions favor the development of this disease. Objective. To determine the incidence and frequency of occurrence of black pod rot of Theobroma cacao fruits at different height ranges, in four ecotopes of cultivated areas in Baracoa, Cuba. Materials and methods. The study was conducted in four cocoa-producing ecotopes in the municipality of Baracoa, Cuba, in May 2023. A total of 385 plants were evaluated in ecotopes with different topography, drainage, humidity, and cocoa varieties. Incidence was calculated as (infected trees/observed trees) × 100 %, while frequency of occurrence measured the distribution of infection across height ranges (0-1.5 m, 1.5-3 m, >3 m). The analysis included Pearson’s chi-square test, the Phi coefficient, and the Z-test with Bonferroni correction. Results. The overall incidence was 76.26 %, with a significant difference among ecotopes (E1 = 83.33 % and E4 = 65 %; p = 0.036), with a weak association (Phi = 0.087). Infection was concentrated at 1.5-3 m in height (60.31 %), exceeding the 0-1.5 m (30.29 %) and >3 m (27.15 %) strata. Conclusions. The incidence of the disease in the cocoa ecotopes of Baracoa was high, mainly on west-facing slopes, indicating that topographic characteristics influence its spread. The observed frequency of occurrence suggests that management practices condition the microclimate and favor pathogen development. Overall, topographic, environmental, and management factors contribute to disease dynamics.